THE INCLUSION OF STUDENTS WITH AUTISM SPECTRUM DISORDER IN MATHEMATICS EDUCATION: CHALLENGES AND POSSIBILITIES IN MIDDLE SCHOOL - Costa, Nilson Santos; Gomes, Adriana Moraes; de Oliveira, Jessica Martins; Vituriano, Hercília Maria de Moura; dos Santos, Jacy Pires; Cabral, Walter Reis (Seven Editora, 2025)
There are gaps between the advancement of the legal framework for inclusive education and the practices actually implemented in schools, especially in Mathematics classes. In this context, this study aims to analyze the challenges and possibilities of including students with Autism Spectrum Disorder (TEA) in the teaching of Mathematics in Middle School. To this end, a qualitative, bibliographic, and exploratory-descriptive study was conducted, involving the analysis of scientific publications, official documents, and national and international empirical studies, organized into thematic categories related to barriers, pedagogical strategies, and institutional conditions. It is observed that the inclusion of students with TEA is still marked by teacher insecurity, gaps in initial and continuing training, insufficient resources, and the predominance of traditional methodologies, although successful experiences have been identified that are supported by visual approaches, concrete materials, structured routines, assistive technologies, and collaborative planning. It is concluded that making inclusion in Mathematics effective requires systematic investment in teacher training, curricular flexibility, improvement of working conditions, and the strengthening of inclusive pedagogical practices, so that Mathematics teaching becomes a space of participation, meaningful learning, and respect for diversity for all students. DOI: https://doi.org/10.56238/sevened2025.038-053